Plant secondary metabolites enhance survival and pathogen tolerance in the European honey bee: a structure-function study - Hogeboom, Alison, author; Norton, Andrew, advisor; Bjostad, Louis, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2019)
Adequate nutrition is essential for European honey bee (Apis mellifera) colony growth, and productivity, yet foraging limitations resulting from factors such as habitat loss often lead to dietary deficiencies. Plant secondary metabolites are key constituents of floral nectar that support physiological processes in honey bees, however, these compounds are only available to bees with access to a diversity of floral resources. Furthermore, the relationship between different classes of plant secondary metabolites and their function within honey bee diets requires further investigation. Using a structure-function framework, we evaluated whether four structurally similar plant secondary metabolites found in the nectar of common agricultural crops elicit comparable effects on honey bee survival and pathogen tolerance. The addition of plant secondary metabolites to artificial nectar solution enhanced median survival, in some cases more than doubling the lifespan of worker honey bees. Moreover, plant secondary metabolites demonstrated nutraceutical effects, and sometimes elicited medicinal effects on honey bees infected with Nosema ceranae. Our findings provide a platform to identify plant secondary metabolites which can augment current management techniques to support the long-term sustainability of the apiculture industry.
Keywords: honey bee; plant secondary metabolites; nosema ceranae; chemical ecology